2007
DOI: 10.1016/j.jchromb.2007.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Detection of altered N-glycan profiles in whole serum from rheumatoid arthritis patients

Abstract: Altered N-glycosylation occurs in many diseases. In rheumatoid arthritis (RA), for example, reduction in galactose residues in IgG and an increase in fucose residues in α1-acid glycoprotein have been observed. To further analysis of N-glycans in disease, we show N-glycan profiling from whole serum employing reversed phase high performance liquid chromatography/negative-ion mode by sonic spray ionization ion trap mass spectrometry with pyridylamination. Profiles from female 15 RA patients and 18 aged-matched he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…This study demonstrated the detailed structures including the linkage information and the abundance changes of sialylated glycans in RA serum. The differences of specific glycans and the significant increase of tri- and tetra-sialylated glycoforms as well as fucosylation was consistent with previous works [27]. These observed changes of glycosylation demonstrate the possibility of using glycans as biomarker for RA diagnosis in the future.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This study demonstrated the detailed structures including the linkage information and the abundance changes of sialylated glycans in RA serum. The differences of specific glycans and the significant increase of tri- and tetra-sialylated glycoforms as well as fucosylation was consistent with previous works [27]. These observed changes of glycosylation demonstrate the possibility of using glycans as biomarker for RA diagnosis in the future.…”
Section: Resultssupporting
confidence: 91%
“…Aberrant glycosylation happens on several important serum glycoproteins, such as IgG, haptoglobin (Hp), and alpha-1-acid glycoprotein (AGP) in RA patients [2426]. Previous studies investigated the N-glycan patterns in the serum of RA patients [2729]. However, the comparison of glycans between RA patients and healthy controls in detail has not yet been investigated, since the isomeric glycans were difficult to be identified and annotated.…”
Section: Introductionmentioning
confidence: 99%
“…Nakagawa et al employed a more traditional reversed phase LC/MS-based approach to analyze N-glycan isomers from rheumatoid arthritis patients; however, glycans had to be desialylated and then derivatized prior to analysis. 26 Bones et al attempted a non-MS approach involving ultra performance LC and fluorescence detection of labeled N-glycans. 27 In contrast, Prien et al employed a wholly non-chromatographic approach using MS n to differentiate structural isomers for a small number of derivatized glycans isolated from tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in glycans in cancer cells were shown and linked with cell adhesion, metastasis, and oncogenic transformation, and those in the endothelium of inflammation tissue were shown and linked with leukocyte homing (9). Moreover, the structural changes in the N-glycan of serum proteins are associated with some diseases, e.g., agalactosylation (35) and fucosylation (14) of IgG in rheumatoid arthritis (32) and ␣1,6-fucosylation of ␣-fetoprotein in hepatocellular carcinoma (3,4). Those are suggested to be useful for clinical markers (2).…”
mentioning
confidence: 99%